Magneto-Impedance Effect of Composite Wires Prepared by Chemical Plating under DC Current - Chen, D. L.; Li, X.; Pan, H. L.; Luan, H. Y.; Zhao, Z. J. (Nano-Micro Letters, 2014)
CuBe composite wires of 100 μm in diameter coated with a layer of NiCoP were prepared by a chemical plating method under DC current (CPUDC). The influences of DC current on coating morphology, deposition rate, composition, giant magneto-impedance (GMI) effect and magnetic properties were investigated. It was shown that the circumferential domain structure of coating layer was induced by the DC current going through the wires. A maximum GMI ratio of 870% was obtained in the composite wire prepared under 150 mA and tested at 180 kHz. It is 30 times higher than that of the composite wire plated in the same condition by conventional chemical plating method, indicating that CPUDC is an easy and effective approach to obtain composite wires and its applications will be further extended on magnetic sensors.